Keragaman Genetik, Heritabilitas dan Korelasi Antar Karakter Tanaman Tomat di Dataran Rendah - Saputra, Helfi Eka; Syukur, Muhamad; Aisyah, Syarifah Iis (Akta Agrosia, 2015)
The main problem in the cultivation of tomato plants in Indonesia are not available varieties of potentially high yield, good fruit quality and can adapt well to the low altitude. Therefore, the assembly of superior varieties of tomatoes low altitude are needed. Research objective is to determine the genetic diversity, heritability and determine the relationship between the characters for the assembly of tomato varieties are high yielding lowland. The experiments were performed using the Randomized Complete Block Design the single factor that genotype by 20 with three replications. The results showed there are six characters that have a broad genetic diversity and high heritability, namely plant height, leaf length and width, number of fruits per plant, fruit length and width. Correlation analysis between characters indicate the number of fruits per plant suitable for use as a character selection for yield potential. Number of fruits per plant of the highest owned by IPB T23. Fruit weight per plant of the highest owned by IPB T 1.